SENGKETA WAKAF DAN PENYELESAIANNYA DALAM PERSPEKTIF UNDANG-UNDANG WAKAF NO 41 TAHUN 2004 - ahmad zaenur rosyid (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2012)
Religious Endowments (waqf) that have been developed in several countries and Indonesia have important role for the social welfare of the people. However, as the endowment is a part of the people asset management, it always brings complexity and problematic atmospheres in its management. One problem arises is the waqf dispute, which usually starts from the traditional unproductive management resulting in being sold by the unresponsible individuals. This paper attempts to elaborate and trace out the disputes in term of the responsibilities of each body involved in the endowments process. Based on the research that emphesaizes on the legal-formal norm approach, it is already mentioned that the Waqf Act No. 41of 2004 has provided complete and comprehensive provisions governing the issues of the endowment and its arising disputes. The dispute may arise from the waqf provider, the Nazir (the officer of the Endowments Pledge Deed), Waqf Board of Indonesia or the Shariah Board of Finance. This endowment disputes ranging (19%) were brought before the Religious Affairs Court as compared to Shariah economic matters (12), inheritance (1373), testament (25), grants (46), or zakat or infaq shodaqah (25).